2014
DOI: 10.5406/amerjpsyc.127.2.0191
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenology of Lucid Dreaming: An Online Survey

Abstract: In lucid dreams the dreamer is aware that he or she is dreaming. Although such dreams are not that uncommon, many aspects of lucid dream phenomenology are still unclear. An online survey was conducted to gather data about lucid dream origination, duration, active or passive participation in the dream, planned actions for lucid dreams, and other phenomenological aspects. Among the 684 respondents who filled out the questionnaire, there were 571 lucid dreamers (83.5%). According to their reports, lucid dreams mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
96
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 37 publications
10
96
2
1
Order By: Relevance
“…In many cases the participants forgot to signal after becoming lucid in a dream. Our recent survey, which included 571 lucid dreamers, revealed that waking memory recall is often impaired in lucid dreams -in average lucid dreamers are able to recall only a half those actions that they plan in wakefulness for accomplishment in lucid dreams (Stumbrys, Erlacher, Johnson, & Schredl, 2013). In the present study these numbers were markedly lower.…”
Section: Discussioncontrasting
confidence: 65%
“…In many cases the participants forgot to signal after becoming lucid in a dream. Our recent survey, which included 571 lucid dreamers, revealed that waking memory recall is often impaired in lucid dreams -in average lucid dreamers are able to recall only a half those actions that they plan in wakefulness for accomplishment in lucid dreams (Stumbrys, Erlacher, Johnson, & Schredl, 2013). In the present study these numbers were markedly lower.…”
Section: Discussioncontrasting
confidence: 65%
“…In a study that explored LD phenomenology, it was found that women had taken a less active role in developing dream plots than men during LD (16). This finding might be one of the possible explanations for having more control subscale points in males compared with females.…”
Section: Discussionmentioning
confidence: 95%
“…Also age, gender, some drugs and foods, stress, insomnia, too much study and work, and sexual intercourse are associated factors (8). In addition, Stumbrys et al (9) have reported that lucid dream phenomenology might be different between sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness indeed differs from lucidity in the sense that mindfulness is non-judgemental and non-reactive (Malinowski, 2008). A mindful person does not have explicit intention to control his or her experience but rather to observe it, while in lucid dreams the dreamer is usually activespontaneously sets new goals for actions and tries to execute them (Stumbrys et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the hypothesized relationship between mindfulness while awake and lucid dreaming the present study aimed to overcome previous limitations by exploring this relationship in a sub-population with a high likelihood of lucid dreams (cf. Stumbrys, Erlacher, Johnson, & Schredl, 2014). Furthermore, we investigated the moderating influence of meditation practice in the relationship between mindfulness and dream lucidity.…”
Section: Introductionmentioning
confidence: 99%